Size and crystallinity-dependent magnetic properties of CoFe2O4 nanocrystals - Chia, Chin Hua; Zakaria, S.; Yusoff, Maisarah; Goh, S.C.; Haw, Choon Yian; Ahmadi, Shideh; Huang, Nay Ming; Lim, Hong Ngee (Elsevier, 2010)
CoFe2O4 nanocrystals were synthesized by a wet chemical coprecipitation approach. In order to investigate the effect of degree of crystallinity and mean crystallite size of CoFe2O4 nanocrystals on the magnetic properties, a series of CoFe2O4 samples with different degree of crystallinity and mean crystallite size were produced by varying the synthesis and subsequent calcination temperatures. The higher synthesis and subsequent calcination temperatures have resulted in greater degree of crystallinity and bigger mean crystallite size of CoFe2O4 nanocrystals. The VSM studies showed that the saturation magnetization (Ms) and coercivity (Hc) of the CoFe2O4 nanocrystals possessed a linear relationship with the mean crystallite size.